Evolution and taxonomic classification of alphapapillomavirus 7 complete genomes: HPV18, HPV39, HPV45, HPV59, HPV68 and HPV70. - Zigui Chen; Mark Schiffman; Rolando Herrero; Rob DeSalle; Kathryn Anastos; Michel Segondy; Vikrant V Sahasrabuddhe; Patti E Gravitt; Ann W Hsing; Robert D Burk (PLoS ONE)
Background The species Alphapapillomavirus 7 (alpha-7) contains human papillomavirus genotypes that account for 15% of invasive cervical cancers and are disproportionately associated with adenocarcinoma of the cervix. Complete genome analyses enable identification and nomenclature of variant lineages and sublineages. Methods The URR/E6 region was sequenced to screen for novel variants of HPV18, 39, 45, 59, 68, 70, 85 and 97 from 1147 cervical samples obtained from multiple geographic regions that had previously been shown to contain an alpha-7 HPV isolate. To study viral heterogeneity, the complete 8 kb genome of 128 isolates, including 109 sequenced for this analysis, were annotated and analyzed. Viral evolution was characterized by constructing phylogenic trees using maximum-likelihood and Bayesian algorithms. Global and pairwise alignments were used to calculate total and ORF/region nucleotide differences; lineages and sublineages were assigned using an alphanumeric system. The prototype genome was assigned to the A lineage or A1 sublineage. Results The genomic diversity of alpha-7 HPV types ranged from 1.1% to 6.7% nucleotide sequence differences; the extent of genome-genome pairwise intratype heterogeneity was 1.1% for HPV39, 1.3% for HPV59, 1.5% for HPV45, 1.6% for HPV70, 2.1% for HPV18, and 6.7% for HPV68. ME180 (previously a subtype of HPV68) was designated as the representative genome for HPV68 sublineage C1. Each ORF/region differed in sequence diversity, from most variable to least variable: noncoding region 1 (NCR1) / noncoding region 2 (NCR2) > upstream regulatory region (URR) > E6 / E7 > E2 / L2 > E1 / L1. Conclusions These data provide estimates of the maximum viral genomic heterogeneity of alpha-7 HPV type variants. The proposed taxonomic system facilitates the comparison of variants across epidemiological and molecular studies. Sequence diversity, geographic distribution and phylogenetic topology of this clinically important group of HPVs suggest an independent evolutionary history for each type.